WHAT ARE THE UNDERPINNING PREFERENCES OF THE PRACTICAL APPROACH TO DEVELOPING ENVIRONMENTAL GEOGRAPHY REFERENCE BOOKS IN UNIVERSITY? - Fahrudi Ahwan Ikhsan; Sumarmi Sumarmi; Sugeng Utaya; Agus Sugiarto (GeoEco, 2025)
The need to analyse environmental geography reference books in tertiary institutions sets the stepping stones for the book writer’s consideration. Students’ needs are essential in investigating the initial key stages of developing a new reference book. This study aimed to analyse the needs of content preferences, geography skills, and design formats of Environmental Geography reference books. It employed a quantitative descriptive method with an online survey through Google Forms. Using the snowball technique, the research subjects were students enrolled in Environmental Geography courses in Indonesia during the odd semester in 2022. Data were analysed descriptively. The findings indicated that Environmental Geography knowledge, geography skills, and design were key requirements for developing reference books. The students were primarily concerned with content-based and geography skills in environmental geography, not with lectures. The development of digital technology has no impact on students because of the prevalence of printed versions of reference books. Implications of the results were the key to integrating content, skills, geography, and design in creating learning resource products in Indonesia.